More on Faraday's and Lenz's laws - Qualitative demonstrations - Hessel, Roberto [UNESP] (American Association of Physics Teachers (AAPT), 2011)
A large variety of simple setups for demonstrating Faraday's and Lenz's laws have been described in the literature.1-4 For a few semesters, we tested some of these setups, especially those suggested in Ref. 1, but recently we decided to develop our own version.